2004
DOI: 10.1097/00001721-200408000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trans-resveratrol on the thrombogenicity and atherogenicity in apolipoprotein E-deficient and low-density lipoprotein receptor-deficient mice

Abstract: Resveratrol is one of the major polyphenolics in red wine that has been shown to exert the preventive effects against cardiovascular diseases. The effect of trans-resveratrol (t-RES) administered as an ingredient of the diet on the atherothrombotic tendency was assessed in genetically hypercholesterolemic mice after laser-induced damage on endothelium. Mice lacking both apolipoprotein E and low-density lipoprotein receptor (apoE-/-/LDLR-/-) were fed with a high-fat diet with or without t-RES (9.6 and 96 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 23 publications
2
46
0
2
Order By: Relevance
“…Although a controversy still exists in terms of the role of IL-6 in atherogenesis, resveratrol itself was reported to attenuate atherogenesis in apolipoprotein E knockout mice without a significant change in the blood lipid profile, 32 which may indicate the therapeutic or preventive implication of resveratrol in atherosclerotic cardiovascular diseases. Our study suggests that this atheroprotective effect of resveratrol may involve the inhibition of the Ang II function and the resultant suppression of IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…Although a controversy still exists in terms of the role of IL-6 in atherogenesis, resveratrol itself was reported to attenuate atherogenesis in apolipoprotein E knockout mice without a significant change in the blood lipid profile, 32 which may indicate the therapeutic or preventive implication of resveratrol in atherosclerotic cardiovascular diseases. Our study suggests that this atheroprotective effect of resveratrol may involve the inhibition of the Ang II function and the resultant suppression of IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that resveratrol reduced the atherosclerotic area and the size of the thrombus generated by the laser. 113 The possible mechanism is the inhibition of COX-1 and COX-2 by resveratrol. The synthesis of eicasoinds and leukotrienes from arcahidonic acid is also linked to platelet aggregation.…”
Section: Effect On Platelet Aggregationmentioning
confidence: 99%
“…Fukao i wsp. [13] przeprowadzili badania z udziałem myszy apo E -/ -LDL (z wyciszonym genem odpowiedzialnym za produkcję apolipoproteiny E i receptora, liporotein o małej gęstości). Przez 8 tygodni podawano tym zwierzętom dietę eksperymentalną wysokotłuszczową z dodatkiem resweratrolu w ilości 9,6 mg/kg m.c.…”
Section: Resweratrol a Ryzyko Przewlekłych Chorób Niezakaźnychunclassified
“…spowodował znaczące zmniejszenie nasilenia procesu zapalnego, nacieku neutrofilowego i aktywności cytokin [23]. Działając razem z kwercetyną, resweratrol blokował uwalnianie z ludzkich komórek nabłonka oddechowego mediatorów stanu zapalnego: interleukiny 8 (Il-8), która "przyciąga" komórki odpornościowe oraz czynnika stymulujące-go kolonie granulocytów i makrofagów (GM-CSF) [10,13].Naukowcy zbadali również wpływ resweratrolu na wirusy. Stwierdzono, że następstwem oddziaływania tego związku jest hamowanie replikacji wirusa cytomegalii (CMV) [12].…”
unclassified